Care of Baby Chicks - Christopher DeCubellis (EDIS)
AN-170, a 3-page illustrated fact sheet by Christopher DeCubellis, provides basic overview of the care of chicks, brooder requirements, space requirements, what to do when chicks arrive, feeding, and keeping chicks healthy. Published by the UF Department of Animal Science, July 2007.